ANALISA LEMAHNYA FUNGSI LEGISLASI DPD RI DALAM SISTEM BIKAMERAL DI INDONESIA - Aditya Adjie Pradana (2023)
This research discusses the weak legislative function of the DPD RI because there was only one bill from the DPD RI which became a law since the inception of the DPD until the 2019 period, there are problems regarding the legislative function of the DPD RI which can be seen from the many bills made by the DPD RI but often If it fails to become a law, the problem is that the researcher explains the factors that influence the weak legislative function of the DPD RI. This research uses descriptive qualitative data collection techniques through interviews and literature studies using the concept of legislative functions and soft bicameral analysis. with the theory of hegemony of power and the theory of a bicameral government system, the final results of this study found that the weak function of this legislation was caused by two factors, namely internal and external factors, internal factors caused by membership of the DPD, the contents of the bill, and finally problems in finalizing and bills, then external factors caused by the constitution and the domination of political parties. As the conclusion of this study, the factor that became the main trigger of the weakness of the DPD RI legislative function was external factors.